Functional writer's cramp as psychogenic focal dystonia - V. A. Tolmacheva; P. G. Yuzbashyan; R. M. Shishorin; B. A. Volel; D. V. Romanov (Неврология, нейропсихиатрия, психосоматика)
We present a description of a functional writer's cramp case. The disease manifested as pain and tension in the right hand when writing; thus, we suspected kinesigenic dystonia in the form of writer's cramp. However, the motor pattern and the presence of additional manifestations made it possible to assume the neurotic nature of hyperkinesis. A psychiatrist diagnosed a combined conversion motor and undifferentiated somatoform disorder as a part of personality dynamics of the dramatic cluster at the involutionary age. Treatment included cognitive-behavioral therapy and periciazine administration with a positive effect. We discuss the aspects of hyperkinesis and mental status, which help differentiate the kinesigenic form of dystonia (writer's cramp) and functional movement disorder.